THE SPECIAL TRIBUNAL FOR THE CRIME OF AGGRESSION AGAINST UKRAINE: NEW FRONTIERS OF INTERNATIONAL JUSTICE - BURMA, SERGII (Ehrlich’s Journal, 2025)
The article presents a comprehensive study of the legal, institutional, and politico-legal foundations of the functioning of the Special Tribunal for the Crime of Aggression against Ukraine, established on 25 June 2025 pursuant to the Agreement between Ukraine and the Council of Europe. The paper examines the reasons for the impossibility of exercising full jurisdiction by the International Criminal Court over the crime of aggression under the current international legal order, particularly in view of the limitations of Article 15 bis of the Rome Statute, the architecture of international justice institutions, and political obstruction within existing institutional mechanisms. It is argued that the establishment of a separate ad hoc mechanism is a necessary yet justified step toward ensuring the inevitability of individual criminal responsibility for violations of jus cogens norms of international law. Based on an analysis of the Tribunal’s Statute, relevant UN General Assembly resolutions, the jurisprudence of ad hoc tribunals, and scholarly doctrine on the crime of aggression, immunities, and transitional justice, the study outlines the Tribunal’s jurisdictional scope, organizational structure, and normative framework. Particular attention is devoted to the issue of immunities of high-ranking state officials, their relation to the principle of sovereign equality of states and to jus cogens norms, as well as to conflicts of jurisdiction between national and international legal mechanisms. The article argues that the Tribunal preserves legal continuity with the traditions of international criminal justice, complements the jurisdiction of the ICC, and has the potential to serve as a model for similar mechanisms in the future. The paper also explores the procedural features of the Tribunal, including the institutions of in absentia proceedings and judges’ separate and dissenting opinions. Certain concerns are raised regarding the legitimacy risks associated with the ad hoc format, in particular the limited participation of states and the dependence on voluntary funding. It is concluded that, despite these challenges, the Tribunal delineates a new conceptual boundary between political expediency and the rule of law in the context of a transforming international legal order.